1999
DOI: 10.1016/s0020-7292(98)00219-7
|View full text |Cite
|
Sign up to set email alerts
|

Laminaria and sulprostone in second trimester pregnancy termination for fetal abnormalities

Abstract: The efficacy and safety of intracervical placement of laminaria and intravenous prostaglandin E2 (sulprostone) infusion for termination of second-trimester pregnancies with abnormal fetuses was investigated. One hundred and six pregnant women at 13-29 weeks' gestation with fetal anomalies underwent laminaria tent insertion into the cervical canal on admission. The next morning, Sulprostone infusion was started at a rate of 16 microg/h and increased by 16 microg/h every 30 min to induce uterine contractions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Among the medicinal methods, one of the methods is the use of misoprostol, which softens the cervix and induces labor pains in the second trimester of pregnancy. 15 One of the mechanical methods is to use devices that slowly dilate the cervix. Ghung et al concluded that the low price, easy insertion method and the ability to remove it quickly are the benefits of laminaria, and this method can be used in abortion treatment in the second trimester.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the medicinal methods, one of the methods is the use of misoprostol, which softens the cervix and induces labor pains in the second trimester of pregnancy. 15 One of the mechanical methods is to use devices that slowly dilate the cervix. Ghung et al concluded that the low price, easy insertion method and the ability to remove it quickly are the benefits of laminaria, and this method can be used in abortion treatment in the second trimester.…”
mentioning
confidence: 99%
“…16 Slow and gradual dilatation of the cervix by laminaria before the beginning of the medical induction of labor reduces the risk of wound and trauma to the cervix. 15,17 Due to the different results in different studies and emphasizing the point that laminaria is a cheap medicine, it has few complications for the patient and also reduces the possibility of trauma to the cervix in patients who are candidates for abortion treatment, we decided to investigate the effects of the medicinal combination of laminaria and Let's compare vaginal misoprostol with letrozole + misoprostol in preparation of cervix in second trimester abortion.…”
mentioning
confidence: 99%